Analysis of the Level of Satisfaction of Using the Majalengka Digital Samsat Website Using the K-Nearest Neighbor Algorithm - Muhammad Abdul Jabbar; Fikri Akbar Falcata Winata; Rifqi Syamsul Fuadi; Ade Taopik Hidayatuloh (Journal of Multimedia Technology and Applied Software, 2025)
The development of mobile applications is currently very rapid. Many applications have emerged with the aim of meeting various human needs, ranging from hobbies, lifestyle, household needs, to religious aspects and others. However, because of the many applications with similar functions, competition between developers is inevitable. They compete to attract user interest by presenting superior features that differentiate their applications from competitors. In this context, sentiment analysis is one of the important methods for understanding how users perceive an application